Si‐, Ge‐, Sn‐Based Anode Materials for Lithium‐Ion Batteries: From Structure Design to Electrochemical Performance. Issue 3 (18th January 2017) - Li, Weihan; Sun, Xueliang; Yu, Yan
Abstract : As state‐of‐the‐art rechargeable energy‐storage devices, lithium‐ion batteries (LIBs) are widely applied in various areas, such as storage of electrical energy converted from renewable energy and powering portable electronic devices and electric vehicles (EVs). Nevertheless, the energy density and working life of current commercial LIBs cannot satisfy the rapid development of these applications. It is urgently required that the electrochemical performance of LIBs, which is mainly determined by the electroactive electrode materials, is improved. However, commercial graphite‐based anode materials deliver a relatively low theoretical capacity of 372 mA h g −1, severely hindering the increase of the energy density of LIBs. Recently, M‐based anode (M represents Si, Ge, and Sn) materials have attracted great attention due to their high theoretical capacity and reasonable anodic voltage. However, the application of M‐based anode materials is seriously limited by a series of several critical problems, such as poor kinetics and huge volume change on cycling. Here, these fundamental problems leading to poor electrochemical performance are discussed, and a series of reasonable nanostructures for M‐based anodes with improved electrochemical performance is summarized, demonstrating that the dimensional control in structure design plays a critical role for solving these problems. Abstract : The advanced structure design of silicon, germanium, and tin as anode materials for lithium‐ion batteries is reviewed. By the rational structure design of dimensional control (i.e., zero (0D), one (1D), two (2D), and three (3D) dimensional structures), the electrochemical performance of Si, Ge, and Sn is improved significantly.